Not Social Welfare but Social Protection Planning: Adult Education as an Alternative for Older People's Wellbeing - Bhattarai, Lok P. Sharma (Economic Journal of Nepal, 2013)
The ever-increasing demands for the payment of old-age pensions have become a serious challenge to public finance in present time. The governments of different countries are looking for alternatives to tackle the problem; but well-accepted, sustainable, inclusive alternatives have remained as a debatable issue. In this article, the Author argues that older people's social security issue must not be dealt with by an exclusively welfare approach; instead, it should be taken as a matter of social protection planning. Adult education has been proposed and discussed as an alternative policy area to focus on which may have the potential to ease the burden of old-age pension in a sustainable way.